Contribution and Efforts of Islamic Boarding Schools In The Mental And Spiritual Development Of Santri At Darus Sholah Islamic Boarding School, Tegal Besar Village, Jember Regency - Yahya, Mohammad (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
Islamic boarding schools are one of the traditional educational institutions that have existed since Indonesia was not yet independent and have developed until now. Its existence greatly influences the dynamics of life in the surrounding community. The research method used is field research, using a qualitative approach, which emphasizes field analysis which will be concluded in the form of deductive and inductive descriptions and explanations that still adhere to scientific studies. The data collection technique in this research is the observation method where the initial observation is by observing the process. education carried out at the Darus Sholah Islamic Boarding School, the researcher used the interview method as an effort to collect data by conducting questions and answers to the management, principal, teachers/clerics, students, and guardians of the students research, and the documentation method was to obtain data such as history, as well as teacher qualifications, the condition of the students, as well as the facilities and infrastructure at the Darus Sholah Islamic Boarding School. Meanwhile, the approach used in this research is a case study with a phenomenological basis, the sample technique chosen is purposive sampling, by extracting data from informants who are considered to know and understand the problem being sought, then the data obtained is analyzed descriptively which tends to be inductive. Based on the results of this research, the contribution and efforts of the Darus Sholah Islamic Boarding School in developing the mental and spiritual development of students are very large. Providing religious values, having a broad perspective in the scope of general science and religion, conveying sensitivity to amar ma'ruf nahi evil towards each other and the environment, Forming the personality of Islamic students who are physically and spiritually balanced, and influential with the many educational institutions that have been established both formal and non-formal education. Keywords: Educational Institutions, Mental And Spiritual Development Of Students